Discrete versus multiple word displays: a re-analysis of studies comparing dyslexic and typically developing children - Zoccolotti, Pierluigi; De Luca, Maria; Spinelli, Donatella (Frontiers in Psychology, 2015)
The study examines whether impairments in reading a text can be explained by a deficit in word decoding or an additional deficit in the processes governing the integration of reading subcomponents (including eye movement programming and pronunciation) should also be postulated. We report a re-analysis of data from eleven previous experiments conducted in our lab where the reading performance on single, discrete word displays as well multiple displays (texts, and in few cases also word lists) was investigated in groups of dyslexic children and typically developing readers. The analysis focuses on measures of time and not accuracy. Across experiments, dyslexic children are slower and more variable than typically developing readers in reading texts as well as vocal RTs to singly presented words; the dis-homogeneity in variability between groups points to the inappropriateness of standard measures of size effect (such as Cohen’s d), and suggests the use of the ratio between groups’ performance. The mean ratio for text reading is 1.95 across experiments. Mean ratio for vocal RTs for singly presented words is considerably smaller (1.52). Furthermore, this latter value is probably an overestimation as considering total reading times (i.e., a measure including also the pronunciation component) considerably reduces the group difference in vocal RTs (1.19 according to Martelli et al., 2014). The ratio difference between single and multiple displays does not depend upon the presence of a semantic context in the case of texts as large ratios are also observed with lists of unrelated words (though studies testing this aspect were few). We conclude that, if care is taken in using appropriate comparisons, the deficit in reading texts or lists of words is appreciably greater than that revealed with discrete word presentations. Thus, reading multiple stimuli present a specific, additional challenge to dyslexic children indicating that models of reading should incorporate this aspect